Error Analysis of Class Management In Implementing Curriculum 13 in Lower Class Elementary School Teachers in The District of Buluspesantren Kebumen - Rokhmaniyah Rokhmaniyah; Kartika Chrysti Suryandari; Joharman Joharman (The Faculty of Teacher Training and Education (FKIP), Universitas Sebelas Maret, Indonesia, 2019)
This article describes the results of research aimed at (1) describing the pattern of classroom management errors in implementing Curriculum 13 in lower grade elementary school teachers, (2) analyzing the causes of classroom management errors in implementing Curriculum 13 in elementary school teachers, and (3) Overcoming mistakes made by lower class teachers in class management. The approach in this study is qualitative with the phenomenological method and action research. The subjects of this study were teachers and students of grades 1, 2, and 3 elementary schools in the Buluspesantren District in the academic year 2018/2019. This research sample used 6 elementary schools that have implemented curriculum 13 revisions from grade 1 to grade 6. Data sources used in this study were principals, teachers and students. The data collection techniques used in this study were interviews, observation, and study of documents. The results found: (1) the pattern of classroom management errors in implementing Curriculum 13 by elementary school lower grade teachers is the use of IT media and learning resources, classroom settings, and the empowerment of high-level thinking, (2) the causes of classroom management errors in implementing curriculum 13 by Teachers under elementary school are teachers' creativity is still low so that class management is still traditionally patterned (3) how to correct classroom management errors in implementing curriculum 13 by teachers under elementary schools is by conducting school action research.